Find all natural numbers (natural numbers include 0) m and n satisfying the expression below:
2 m + 2 0 1 9 = ∣ n − 2 0 2 0 ∣ + n − 2 0 2 0
Type your answer as m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For n ≤ 2 0 2 0 we have 2 m + 2 0 1 9 = 0 which has no solutions. For n > 2 0 2 0 we have 2 n − 2 m = 6 0 5 9 ⟹ n = 2 2 m + 6 0 5 9 n can only be an integer when 2 m is odd, this only happens when m = 0 and n = 3 0 3 0 .
So we’re left with m + n = 0 + 3 0 3 0 = 3 0 3 0
First, it's clearly that RHS is even for all natural number of n . Hence, LHS must be even too. Then, assume that m ≥ 1 . From here, we get that 2 m + 2 0 1 9 is odd, contradiction. Hence, m = 0 , so we get 2 0 2 0 = ∣ n − 2 0 2 0 ∣ + n − 2 0 2 0 . Now, assume that ∣ n − 2 0 2 0 ∣ = 2 0 2 0 − n . From here, we get that 2 0 2 0 = 0 , contradiction. Hence, ∣ n − 2 0 2 0 ∣ = n − 2 0 2 0 , so we get 2 0 2 0 = 2 n − 4 0 4 0 ⟹ n = 3 0 3 0 ⟹ m + n = 0 + 3 0 3 0 = 3 0 3 0 .
Problem Loading...
Note Loading...
Set Loading...
Firstly, note that the right-hand side of the given equation is even for all n . This means that the left-hand side is also even, and so 2 m is odd; it follows that any solution must have m = 0 , so the left-hand side must be 2 0 2 0 .
Because of the absolute value function on the right-hand side, we'll consider the cases n ≤ 2 0 2 0 and n > 2 0 2 0 separately.
Case n ≤ 2 0 2 0 :
The equation becomes 2 0 2 0 = ( 2 0 2 0 − n ) + n − 2 0 2 0 = 0 , which is clearly absurd. So there are no solutions in this case.
Case n > 2 0 2 0 :
The equation is now 2 0 2 0 = ( n − 2 0 2 0 ) + n − 2 0 2 0 = 2 n − 4 0 4 0 , which has the unique solution n = 3 0 3 0 . The only possible solution pair is ( m , n ) = ( 0 , 3 0 3 0 ) , giving the answer 3 0 3 0 .